Factores relacionados a la coinfección VIH/TBC en pacientes del Hospital Regional de Loreto - Pasquel Silva, Sonia (2023)
The objective of the research was to determine the factors that are related to HIV/TB coinfection in patients of the Regional Hospital of Loreto. The quantitative method and the non-experimental descriptive correlational, retrospective design were used. The population and sample were 80 patients determined by convenience. The technique was documentary review and the instruments were: Sociodemographic factors and treatment compliance data sheet and the HIV/TB coinfection identification data sheet. For the correlational analysis, the Chi Square statistical test was used with a significance level of α = 0.05. The results show that 40% were between 20 and 35 years old, 63.7% were men, 67.5% reached secondary school, 48.8% had informal work, 47% had an income of less than 500 soles, 61.3% lived in a marginal urban area, 42.5% used tobacco, 66.3% did not comply with their treatment and 58.7% did have HIV/TB coinfection. A significant relationship was demonstrated between HIV/TB coinfection and age (p = 0.021), sex (p = 0.004), educational level (p = 0.019), occupation (p = 0.019), origin (p = 0.019), = 0.021) and treatment compliance (p = 0.014). No relationship was found with harmful habits (p = 0.745). In conclusion, age, sex, level of education, occupation, area of residence and compliance with treatment are related to HIV/TB coinfection in patients at the Hospital Regional de Loreto.